2019
DOI: 10.3390/ma12081209
|View full text |Cite
|
Sign up to set email alerts
|

Assessment for Sustainable Use of Quarry Fines as Pavement Construction Materials: Part I—Description of Basic Quarry Fine Properties

Abstract: As a secondary material, quarry fines are a valuable material to be reused for many purposes in civil engineering projects. The aggregate source depletion, especially the lack of high quality aggregates as expected in the future, as well as the demand for a carbon-neutral society and circular economy, also promotes the high-volume utilization of secondary materials such as quarry fines. The aim of this study is to do a feasibility assessment including a series of laboratory tests and analyses to evaluate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…As verified and stated in the previous research published earlier [11], basic properties of the unbound quarry fine materials have been investigated by a series of laboratory tests and analysis. Based on the particle distribution information obtained from both sieving and hydrometer methods, as well as the frost heave test results, it was found that the unbound quarry fines of 0–4 mm are prone to be frost-susceptible.…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…As verified and stated in the previous research published earlier [11], basic properties of the unbound quarry fine materials have been investigated by a series of laboratory tests and analysis. Based on the particle distribution information obtained from both sieving and hydrometer methods, as well as the frost heave test results, it was found that the unbound quarry fines of 0–4 mm are prone to be frost-susceptible.…”
Section: Introductionmentioning
confidence: 55%
“…In the previous study [11], virgin quarry fine materials of 0 to 4 mm grain size, produced at the quarry in Koskenkylä by Destia Oy, were collected and investigated through a series of laboratory tests. The host rock of quarry is very high quality rock with extremely good abrasion value [16], which is only about 1% of what Finnish host rock material fulfills.…”
Section: Virgin Quarry Fine Materialsmentioning
confidence: 99%
See 3 more Smart Citations